Africa’s Oil Coast: Reflecting on Relations Among Gulf of Guinea Coast States: Relations in the Gulf of Guinea Coast - Nwamuo, Bright; Alaku, Emmanuel; Ani, Uchenna U. (Advances in Social Sciences Research Journal, 2021)
The Gulf of Guinea coast is a region endowed with petroleum resources and this has brought prominence to the region as major oil consumers and oil companies are found in the region. The region has become an alternative source of energy to the Middle East and demand for the region’s oil has continued to increase. Different countries make up the Gulf of Guinea with different colonial background, economic interest and levels of suspicion. This paper examines relations among these countries and its implication on their oil endowment and security. It suggests efforts that the Gulf of Guinea states can make to strengthen relations/cooperation among these states as this will enhance economic the development of the Gulf of Guinea coast.